Design and implementation of AMQP-based campus message bus system - Wei-xin WU; Yu WANG; Xing-wei WANG (Tongxin xuebao)
For the strong coupling complex dependencies between applications in the traditional digital campus system,a digital campus message bus system was designs and implemented based on AMQP.In this system,the message bus is the digital messaging middleware between digital campus applications which simplifies application development logic and reduces the coupling dependencies between applications.Practical application of this system shows that the structure is suitable for the construction of digital campus,so that each application of digital campus will be easier to be managed and expanded.